Taxonomia e filogenia das espécies de Dasyloricaria Isbrücker & Nijssen, 1979 (Siluriformes: loricariidae) - Burbano, Alejandro Londoño (2012)
A taxonomic revision and phylogenetic analysis of the genus Dasyloricaria were performed. This group belongs to the catfish family Loricariidae, subfamily Loricariinae and its distribution is strictly Trans Andean. Within the loricariines, individuais in Das yloricaría can reach more than 20 cm of Standard Length. The taxonomic revision was based on 142 specimens of the main river basins of Colombia, Venezuela and Panama, from which were obtained rneasurements and counts. In this study are proposed as valid the species DasylorÊcaría jilarnentosa (Steindachner) from the upper, middie and lower Magdaiena River, lower Cauca River and Sinú River basin in Colombia, and the Maracaibo Lake basin m Venezuela, and Dasyloricaria latiura (Eigenmann & Vance) from the Atrato River basin in Colombia and Tuyra River basin m Panama, as well as a description of a new species, Dasyloricaria n. sp., from the middie and upper portions of the Magdaiena River, Coiombia. Redescriptions of the previousiy described species and the description of the new species are presented, including diagnosis, color in alcohol, distribution, sexual dimorphism, comments on each species, and an identification key of the species. After the taxonomic revision, a phylogenetic analysis was conducted based on 187 morphological characters (osteology and extemal morphology) and 23 terminal taxa. Species belonging to five subfamilies of the Loricariidae were included: Dasyloricaria filarnentosa, D. latiura, Dasyloricaria n. sp, Rineloricaria strigilata, R. microlepidogaster, Spatuloricaria sp. Tocantins, Spatuloricaria sp. Xingu, Ixinandria steinbachi, Loricaria cataphracta, L. clavipinna, Pseudoloricaria sp., Pseudoherniodon sp., Loricariichthys anus, Hemiodontichthys acipenserinus, Harttia loricarformis, Siurisorna rostratum, S. robustum (Loricariinae), Hypostomus pyrineusi, Ancistrus reisi (Hypostominae), Eurycheilichthys pantherinus, Otocinclus xakriaba (Hypoptopomatmae), Neoplecostomus microps (Neoplecostominae), and Delturus brevis (Delturinae). Were obtained three equaily most parsimonious trees of 1006 steps each, consistency index of 0.34 and retention index of 0.52. Dasyloricaria was recovered as a monophyletic unit, presenting nine unique synapomorphies. Spatuloricaria is proposed as the sister group of Dasyioricaria. This ciade is supported by tbree unique synapomorphies, and was observed to be the most derived clade within the analysis. Rineloricariina sensu Isbrücker was not recovered as inonophyletic. Relationships between Rineloricaria and (Spatuloricaria + Dasyloricaria) vere not resolved, even when they were found related within the analysis. Harttiini is found as monophyletic, including the genera Harttia and Sturisoma. Also, both Loricariini and Loricariinae are recovered as monophyletic.